Vapor-liquid equilibrium data for binary mixtures of dimethyl carbonate with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate at 93.13 kPa - Mali, Nilesh A.; Yadav, Satyajeet S.; Ghuge, Pravin D.; Joshi, Sunil. S. (Journal of Chemical and Engineering Data, 2017)
Isobaric vapor-liquid equilibrium (VLE) data was measured at the local atmospheric pressure of 93.13 kPa for the binary systems of dimethyl carbonate (DMC) with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate using a dynamic recirculation still. VLE data was generated in the form of T-x,y and was checked for thermodynamic consistency using the Herington area test, Van Ness test, and mean absolute deviation between experimental and calculated total pressure and vapor phase composition. Data for all pairs meet the criteria for thermodynamic consistency and were found suitable for process modeling. Binary interaction parameters for the Wilson, nonrandom two-liquid (NRTL), and universal quasichemical (UNIQUAC) activity coefficient models were determined using the objective function of minimizing the deviation between the experimental and the calculated vapor phase composition and total pressure. For all binary systems, Wilson, NRTL, and UNIQUAC models gave good predictions. Azeotropic behavior was observed for the isopropyl acetate-DMC pair at 357.8 K and 0.6 mole fraction of isopropyl acetate.